The Epstein-Barr virus-encoded nuclear antigen EBNA-5 accumulates in PML-containing bodies. - Szekely, L (1996)
EBNA-5 is one of the Epstein-Barr virus (EBV)-encoded nuclear proteins required for immortalization of human B lymphocytes. In the nuclei of EBV-transformed lymphoblastoid cell lines EBNA-5 is preferentially targetted to distinct nuclear foci. Previously we have shown (W.Q. Jiang, L. Szekely, V. Wendel-Hansen, N. Ringertz, G. Klein, and A. Rosen, Exp. Cell Res. 197:314-318, 1991) that the same foci also contained the retinoblastoma (Rb) protein. Using a similar double immunofluorescence technique, we now show that these foci colocalize with nuclear bodies positive for PML, the promyelocytic leukemia-associated protein. Artificial spreading of the chromatin by exposure to the forces of fluid surface tension disrupts this colocalization gradually, suggesting that the bodies consist of at least two subcomponents. Heat shock or metabolic stress induced by high cell density leads to the release of EBNA-5 from the PML-positive nuclear bodies and induces it to translocate to the nucleoli. In addition to their presence in nuclear bodies, both proteins are occasionally present in nuclear aggregates and doughnut-like structures in which PML is concentrated in an outer shell. Nuclear bodies with prominent PML staining are seen in resting B lymphocytes. This staining pattern does not change upon EBV infection. In freshly infected cells EBNA-5 antigens are first distributed throughout the nucleoplasm. After a few days intensely staining foci develop. These foci coincide with PML-positive nuclear bodies. At a later stage and in established lymphoblastoid cell lines EBNA-5 is almost exclusively present in the PML-positive nuclear foci. The colocalization is restricted to EBV-infected human lymphoblasts. The data presented indicate that the distinct EBNA-5 foci are not newly formed structures but the result of translocation of the viral protein to a specialized domain present already in the nuclei of uninfected cells.